NAADP influences excitation-contraction coupling by releasing calcium from lysosomes in atrial myocytes. - Collins, T; Bayliss, R; Churchill, G; Galione, A; Terrar, D (2011)
In atrial myocytes, the sarcoplasmic reticulum (SR) has an essential role in regulating the force of contraction as a consequence of its involvement in excitation-contraction coupling (ECC). Nicotinic acid adenine dinucleotide phosphate (NAADP) is a Ca(2+) mobilizing messenger that acts to release Ca(2+) from an acidic store in mammalian cells. The photorelease of NAADP in atrial myocytes increased Ca(2+) transient amplitude with no effect on accompanying action potentials or the L-type Ca(2+) current. NAADP-AM, a cell permeant form of NAADP, increased Ca(2+) spark amplitude and frequency. The effect on Ca(2+) spark frequency could be prevented by bafilomycin A1, a vacuolar H(+)-ATPase inhibitor, or by disruption of lysosomes by GPN. Bafilomycin prevented staining of acidic stores with LysoTracker red by increasing lysosomal pH. NAADP-AM also produced an increase in the lysosomal pH, as detected by a reduction in LysoSensor green fluorescence. These effects of NAADP were associated with an increase in the amount of caffeine-releasable Ca(2+) in the SR and may be regulated by β-adrenoceptor stimulation with isoprenaline. These observations are consistent with a role for NAADP in regulating ECC in atrial myocytes by releasing Ca(2+) from an acidic store, which enhances SR Ca(2+) release by increasing SR load.